Strong relationship between coral bleaching and growth anomalies in massive Porites - TIM R. McCLANAHAN; E. WEIL; J. MAINA (Global Change Biology, 2009)
Reports of coral diseases are increasing and may result from human land use and climate change conditions such as increased water temperature, coral bleaching, runoff from land, and changes in the ecology of heavily fished reefs. We examined a stable coral syndrome or a growth anomaly [ Porite growth anomaly (PGA)] (skeletal tissue anomaly, hyperplasia, or ‘tumor’) that was present in 0–15% of massive Porites colonies in 12 Kenyan reef lagoons. At the level of the calice morphology, this growth anomaly showed larger calices with less distance between calices and some calices with higher than normal numbers of septa, which indicate the influence of microboring organisms. Scanning electron micrographs of affected corals revealed a high abundance of fungal hyphae, a potential microboring pathogenic agent. To test the hypothesis that the PGA covaries with environmental variables, we evaluated its prevalence in relationship to 16 parameters of water quality, temperature, intensity of bleaching, benthic composition, and management at the end of the 2005 warm season. Stepwise regression models found eight environmental variables significantly associated with the frequency of the PGA, and the site's bleaching intensity was the most strongly associated variable. When bleaching intensity was removed from the dataset, the concentration of phosphorus was the one significant and positively associated variable, which suggest that the other significant environmental variables were associated with bleaching and not the growth anomalies. Our hypothetical model of causation is that the patchy loss of symbionts, often associated with bleaching, reduces calcification, increases susceptibility to pathogens, and allows endolithic fungi to perforate the skeleton creating a porous and anomalous growth of the skeleton. Consequently, we suggest that the frequency of skeletal growth anomalies is expected to increase with the frequency of coral bleaching.